Managing Irrigation in Indian Agriculture Using Fuzzy Logic – A Decision Support System - Suruthi, N; Saranya, R; Subashini, S; Shanthi, P; Umamakeswari, A (International Journal of Engineering and Technology, 2018)
Supplementation of water for irrigation in needed in south India due to uncertainty of monsoon rainfall. This paper proposes a support system to manage the irrigation system based on the information provided by humidity, temperature, soil moisture and weather information. The temperature, humidity and soil moisture data were collected by sensors. The proposed ANFIS based system consists of N inputs and a single output which determines the irrigation time needed for the crop. The experimentation is carried out using real time data collected from the region of VALLAM, located near THANJAVUR. The result helps in determining the time for irrigation which helps in increasing the yield of the crop.Â Â